2019
DOI: 10.1021/acs.jpcb.8b12126
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Rafts: Buffers of Cell Membrane Physical Properties

Abstract: Lateral organization of lipids in the cell membrane appears to be an ancient feature of the cell, given the existence of lipid rafts in both eukaryotic and prokaryotic cells. Currently seen as platforms for protein partitioning, we posit that lipid rafts are capable of playing another role: stabilizing membrane physical properties over varying temperatures and other environmental conditions. Membrane composition defines the mechanical and viscous properties of the bilayer. The composition also varies strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 62 publications
2
32
0
1
Order By: Relevance
“…Furthermore, new insight into the role of rafts was obtained through NSE measurements of the lateral diffusion coefficients in a phase-separated lipid mixture. In agreement with structural and dynamical data from molecular dynamics simulations, the measurements indicate that rafts function as buffers of membrane properties and that a change in the complex lipid compositions in response to a variation in external parameters (such as temperature) may provide an advantageous stabilizing effect 71 .…”
Section: [H1] Key Aspects Of Neutron Scatteringsupporting
confidence: 75%
“…Furthermore, new insight into the role of rafts was obtained through NSE measurements of the lateral diffusion coefficients in a phase-separated lipid mixture. In agreement with structural and dynamical data from molecular dynamics simulations, the measurements indicate that rafts function as buffers of membrane properties and that a change in the complex lipid compositions in response to a variation in external parameters (such as temperature) may provide an advantageous stabilizing effect 71 .…”
Section: [H1] Key Aspects Of Neutron Scatteringsupporting
confidence: 75%
“…The various ways of biochemical acclimatization of lipid structures to maintain functionality as temperature decreases are often gathered under the umbrella term HVA, which include the HPA and the DPB theory (Sinensky, 1974;Lewis et al, 1989;Hazel, 1995). Central to all is the temperature-dependent dynamism in the lipid bilayer (Zehmer, 2005;Nickels et al, 2019). It should be stressed that there are several mechanisms by which proper lipid composition and physical properties are maintained, and that no clear taxonomic patterns exist, i.e., some animal groups employing only a certain acclimatization response (Koštál, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis provides a compelling rationale for numerous observations relating to membrane trafficking, endocytosis, signal transduction, and other processes (Simons and Toomre, 2000;Simons and Ehehalt, 2002;Shaw, 2006;Allen et al, 2007). It has also been suggested that rafts may contribute to the short-term physical stability of the cell membrane by buffering the mechanical properties of the membrane against rapid changes in temperature, local solvents, and other environmental perturbations (Nickels et al, 2019). Experimental evidence describing lipid rafts has been largely inferential due to the limitations of traditional techniques, and it is widely believed that these features are nanoscopic, as well as transient (Mukherjee and Maxfield, 2004;Lingwood and Simons, 2010), making them difficult to detect in vivo.…”
Section: Introductionmentioning
confidence: 94%